The effect of isolated or combined small-sided games and speed endurance training on physical performance parameters in young soccer players - Akdoğan, Erkan (Array, 2021)
The purpose of this study was to investigate the effects of six weeks of small-sided games (SSG), speed endurance (SER) and combined SSG and SER (CT) training programs on sprint, repeated sprint, Yo-Yo intermittent recovery test level 1 (Yo-Yo IR1) and level 2 (Yo-Yo IR2) performance in young soccer players. Forty-one elite young soccer players (body height: 174.0 ± 7.5 cm, body weight: 59.7 ± 9.5 kg, age: 14.6 ± 0.5 years, training age: 7.4 ± 0.6 years) underwent anthropometric measurements before performing 10m and 30m sprint tests, repeated sprint tests, and Yo-Yo IR1 and Yo-Yo IR2. The players were then divided into four groups: the SSG group (SSG; n=11), the SER group (SER; n=10), the CT group (CT; n=11), and the control group (CG; n=9). All groups performed training for six weeks on two days out of the five training days the participants were undertaking.